Respuesta :

Answer:

Yes, the equation is complete.

Step-by-step explanation:

The given quadratic equation, x² + 3x - 10 = 0 is expressed in standard form, ax² + bx + c = 0.

Where: a = 1, b = 3, and c = -10.

Using the quadratic formula:

[tex]x = \frac{-b (+/-) \sqrt{b^{2} - 4ac} }{2a}[/tex]

We can solve for its solution by plugging in the values for a, b, and c.

[tex]x = \frac{-b (+/-) \sqrt{b^{2} - 4ac} }{2a}[/tex]

[tex]x = \frac{-3 (+/-) \sqrt{(3)^{2} - 4(1)(-10)} }{2(1)}[/tex]

[tex]x = \frac{-3 (+/-) \sqrt{9 + 40} }{2}[/tex]

[tex]x = \frac{-3 (+/-) \sqrt{49} }{2}[/tex]

[tex]x = \frac{-3 + 7 }{2}[/tex],  [tex]x = \frac{-3 - 7 }{2}[/tex]

[tex]x = \frac{4}{2} = 2[/tex],[tex]x = \frac{-10 }{2} = - 5[/tex]

Therefore, the solutions of the quadratic equation, x² + 3x - 10 = 0 is:

x = 2, and x = -5

Please mark my answers as the Brainliest, if you find this helpful :)